SNP Discovery for mapping alien introgressions in wheat - Tiwari, Vijay K.; Wang, Shichen; Sehgal, Sunish K.; Vrána, Jan; Friebe, Bernd R.; Kubaláková, Marie; Chhuneja, Praveen; Doležel, Jaroslav; Akhunov, Eduard D.; Kalia, Bhanu; Sabir, Jamal; Gill, Bikram S. (My University, 2014)
Background: Monitoring alien introgressions in crop plants is difficult due to the lack of genetic and molecular mapping information on the wild crop relatives. The tertiary gene pool of wheat is a very important source of genetic variability for wheat improvement against biotic and abiotic stresses. By exploring the 5M[superscript g] short arm (5M[superscript g]S) of Aegilops geniculata, we can apply chromosome genomics for the discovery of SNP markers and their use for monitoring alien introgressions in wheat (Triticum aestivum L). Results: The short arm of chromosome 5M[superscript g] of Ae. geniculata Roth (syn. Ae. ovata L.; 2n = 4x = 28, U[superscript g]U[superscript g]M[superscript g]M[superscript g]) was flow-sorted from a wheat line in which it is maintained as a telocentric chromosome. DNA of the sorted arm was amplified and sequenced using an Illumina Hiseq 2000 with ~45x coverage. The sequence data was used for SNP discovery against wheat homoeologous group-5 assemblies. A total of 2,178 unique, 5M[superscript g]S-specific SNPs were discovered. Randomly selected samples of 59 5M[superscript g]S-specific SNPs were tested (44 by KASPar assay and 15 by Sanger sequencing) and 84% were validated. Of the selected SNPs, 97% mapped to a chromosome 5M[superscript g] addition to wheat (the source of t5M[superscript g]S), and 94% to 5M[superscript g] introgressed from a different accession of Ae. geniculata substituting for chromosome 5D of wheat. The validated SNPs also identified chromosome segments of 5M[superscript g]S origin in a set of T5D-5M[superscript g] translocation lines; eight SNPs (25%) mapped to TA5601 [T5DL · 5DS-5M[superscript g]S(0.75)] and three (8%) to TA5602 [T5DL · 5DS-5M[superscript g]S (0.95)]. SNPs (gsnp_5ms83 and gsnp_5ms94), tagging chromosome T5DL · 5DS-5M[superscript g]S(0.95) with the smallest introgression carrying resistance to leaf rust (Lr57) and stripe rust (Yr40), were validated in two released germplasm lines with Lr57 and Yr40 genes. Conclusion: This approach should be widely applicable for the identification of species/genome-specific SNPs. The development of a large number of SNP markers will facilitate the precise introgression and monitoring of alien segments in crop breeding programs and further enable mapping and cloning novel genes from the wild relatives of crop plants.
Citation: Tiwari, V., . . . & Gill, B. (2014). SNP Discovery for mapping alien introgressions in wheat. BMC Genomics, 15(1), 273-284. https://doi.org/10.1186/1471-2164-15-273
Keywords: Alien introgressions; Wheat; Tertiary gene pool; Aegilops geniculata; Triticum aestivum L